النمو الاقتصادي في سورية ومنعكساته على التشغيل خلال الفترة 2002 حتّى 2009 (باستخدام نموذج مرونة القوى العاملة(MPEM)) - الرّفاعي, عبد الهادي; اسماعيل, عصام; حبيب, غدير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى دراسة دور النمو الاقتصادي في الحدّ من مشكلة البطالة في سورية, وتحديد أهميّة هذا الدّور عبر الزّمن, ودراسة مؤشّر البطالة ودوره في إعطاء صورة عامّة عن واقع التنمية الاقتصاديّة والاجتماعيّة, إضافةً إلى دراسة دور كل قطاع من القطاعات المشكّلة للاقتصاد السّوري في الحدّ من تلك المشكلة من خلال إعداد نموذج مرونة التوظيف, والذي يحدّد المرونة المرافقة لكل قطاع على شكل معاملات تدخل في النموذج, وتتجلّى أهمية هذا البحث من خلال التعريف بماهية البطالة وأنواعها وسبل الحد منها في إطار النموذج المقترح, ومن أهمّ النتائج التي توصّلنا إليها: · هناك نموذج يعبّر عن مرونة التوظيف بحسب القطاعات في سورية · لا تختلف مرونات التوظيف بحسب القطاعات الاقتصاديّة المختلفة. This research aims to study the role of economic growth in decreasing un-employment in Syria. It defines the importance of this role through time, and it studies un-employment indictor and shows its role in giving a general view about the reality of social and economic development. Besides, studying the role of each economic sector, constituting the Syrian economy, in decreasing that problem by designing the Man-Power Elasticity Model (MPEM). This model defines the associate elasticity for each sector. The importance of the research lies in defining the term un-employment and determining the tools needed to decrease it within the suggested frame work of the model. Finally, the most important results we have reached are: · There is a model that describes working elasticity according to economic sectors. · There are no variances among elasticities of different economic sectors.